The Look of a Woman : Facial Feminization Surgery and the Aims of Trans- Medicine - Plemons, Eric, 1977- (Book collections on Project MUSE., 2017)
Eric Plemons explores the ways in which facial feminization surgery is changing the ways in which trans- women are not only perceived of as women, but in the ways it is altering the project of surgical sex reassignment and the understandings of what sex means.